2011
DOI: 10.1080/00224540903510837
|View full text |Cite
|
Sign up to set email alerts
|

The Reverse Double Standard in Perceptions of Student-Teacher Sexual Relationships: The Role of Gender, Initiation, and Power

Abstract: The present study tested the prediction that male teachers are judged more harshly than female teachers for engaging in heterosexual intercourse with a student. One-hundred and eighty-seven adults (116 women, 71 men) evaluated a hypothetical newspaper article describing an alleged student-teacher relationship as part of a 2 (Gender Dyad: Male Teacher/Female Student or Female Teacher/Male Student) x 2 (Initiator: Student or Teacher) between-subjects design. As expected, a reverse sexual double standard was reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…Our findings differ from the results of several recent studies finding that, for some individuals and under some circumstances, men's sexual activity is perceived more negatively than women's, or that women with many sexual partners are perceived positively (Howell et al 2011; Milhausen and Herold 1999; Milhausen and Herold 2002; Papp et al 2015; Zaikman et al 2014). We extend this body of literature by examining perceptions of sexual motives, whereas past research on a reverse sexual double standard has examined perceptions of sexual behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from the results of several recent studies finding that, for some individuals and under some circumstances, men's sexual activity is perceived more negatively than women's, or that women with many sexual partners are perceived positively (Howell et al 2011; Milhausen and Herold 1999; Milhausen and Herold 2002; Papp et al 2015; Zaikman et al 2014). We extend this body of literature by examining perceptions of sexual motives, whereas past research on a reverse sexual double standard has examined perceptions of sexual behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…Researchers have argued that changing personal and cultural expectations about sexuality may lead to rejection of a traditional sexual double standard (Farvid et al 2016; Jackson and Cram 2003; Milhausen and Herold 1999). Prior research supporting this claim has found inconsistent evidence of the sexual double standard (Bordini & Sperb, 2013; Howell et al 2011; Kreager et al 2016; Marks and Fraley 2005; Milhausen and Herold 1999; Papp et al 2015; Zaikman and Marks 2014). The present findings add to this literature, suggesting that the current social climate of hookup culture in emerging adulthood may shift perceptions of sexual motives away from a traditional gendered sexual double standard, and highlighting the role of social and cultural circumstances in explaining attributions related to others’ sexual behaviors and sexual motives.…”
Section: Discussionmentioning
confidence: 97%
“…Although some quantitative research continues to find evidence for the sexual double standard (Bordini and Sperb 2013; Crawford and Popp 2003; England and Bearak 2014), several experimental vignette designs and some attitudinal studies do not document a strong sexual double standard. Instead these latter studies find that young adults are negatively evaluated for permissive sex regardless of gender (Allison and Risman 2013; Gentry 1998; Marks and Fraley 2005), that is, a “weak” double standard whereby the negative evaluations of young men’s permissiveness are only somewhat less than the negative evaluations of young women’s permissiveness (see Bordini and Sperb, 2013, for a review), or even a reverse double standard whereby young men are evaluated more harshly for their sexual behavior than are young women (Howell, Egan, Giuliano, and Ackley 2011; Zaikman and Marks 2014). …”
Section: Sexual Script Theory and Empirical Researchmentioning
confidence: 99%
“…For example, a female teacher described as engaging in sexual activity with a male student was evaluated more positively than a male teacher engaging in sexual activity with a female student (Howell et al 2011). The existence of the reversed double standard may be partially due to the additional and specific information provided about the targets, thus diminishing the stereotypical evaluations associated with the traditional double standard.…”
Section: The Sexual Double Standardmentioning
confidence: 96%